Галина Іванівна Мудрик: життя і досвід мудрої людини - Констанкевич, Ірина Мирославівна; Konstankevich, I. M. (Волинський національний університет імені Лесі Українки, 2012)
Статтю присвячено огляду життя і науково-педагогічної діяльності Г. І. Мудрик - кандидата філологічних наук, доцента, ветерана освіти з 50-літнім стажем роботи у провідному ВНЗ Волині, одного з фундаторів кафедри української літератури в середині 50-х pp. XXст. This article provides an overview of the life and scientific-pedagogical activity of G. I. Mudryk- candidate of philological sciences, senior lecturer, a veteran of education with 50 years experience in the leading University Volyn, one of Fundator chair of Ukrainian literature from the 50s of the twentieth century. Key words: teacher, person, science and teaching experience.
Galina Mudryk: the Life and Experience of a Wise Man
Keywords: викладач; teacher; особистість; person; науково-педагогічний доробок; science and teaching experience